Economic and technological drivers of rural youth engagement in sugar palm agro-industry in South Sulawesi, Indonesia - ERNAWATI ERNAWATI; SYAHIDAH SYAHIDAH; A. MUJETAHID (Smujo International, 2026)
Abstract. Ernawati, Syahidah, Mujetahid A. 2026. Economic and technological drivers of rural youth engagement in sugar palm agro-industry in South Sulawesi, Indonesia. Asian J Agric 10 (1): g100158. https://doi.org/10.13057/asianjagric/g100158. Palm sugar derived from sugar palm (Arenga pinnata) supports rural livelihoods in Indonesia, yet declining youth participation may weaken enterprise regeneration. Youth refer to individuals aged 15-30 years. This study examined how social, economic, and technical (technological capital) factors, as well as environmental factors, are associated with youth involvement in the sugar-palm agroindustry in South Sulawesi, Indonesia. A census-based survey was conducted in Rompegading and Limapoccoe Villages (Maros District) with 51 respondents aged ≥15 years who were already engaged in tapping, processing, or marketing; interpretation emphasizes the youth subgroup where relevant. Indicators were measured using a three-point Likert scale and aggregated into composite indices for each factor and youth involvement. Multiple linear regression was used to assess associations between the factor indices and youth involvement. Technical (technological capital) and economic factors were positively associated with youth involvement, while social and environmental factors were not statistically significant. Findings suggest that youth engagement may be strengthened through practical training, safer and more efficient tools and processing practices, and measures that enhance income predictability and market access. Because the study is cross-sectional and site-specific, the findings should be interpreted as associative; broader, multi-site, and longitudinal studies are recommended to verify and extend these insights.